From the Guest Editor… New Contributions and Reflections on Graph-Based Representations for Decision Analysis - Horvitz, Eric (Journal of Decision Analysis, 2005)
In this second volume of the special issue of Decision Analysis on graph-based representations for decision analysis, we present two articles and four brief invited perspective pieces, capturing personal reflections on the theoretical and practical influences of probabilistic graphical models in several realms.